A look into the ballot box: Gaze following conveys information about implicit attitudes toward politicians. Issue 2 (February 2013) - Liuzza, MarcoTullio; Vecchione, Michele; Dentale, Francesco; Crostella, Filippo; Barbaranelli, Claudio; Caprara, GianVittorio; Aglioti, SalvatoreMaria
Although considered a predominantly automatic social behaviour, gaze following (GF) is sensitive to complex social factors like political affiliation and ideology. The present study aimed to determine whether the differential proneness to in-group leaders' gaze is related to attitudes towards politicians as measured by other implicit procedures. A GF paradigm was used to test the extent to which electors were prone to gaze following when attending to two female candidates who competed for the position of governor in an Italian election campaign. Results showed that GF significantly predicts voting intentions. Also, it was found that GF is significantly and positively correlated with the Implicit Association Test (IAT). Hierarchical multiple regression models illustrated that GF and IAT uniquely predict voting intentions, accounting for a substantial proportion of variance. Thus GF and IAT, even though significantly related, seem to account for different aspects of the attitudes towards candidates. A multivariate regression model showed that, while IAT scores are predicted by explicit emotions toward the candidate, GF is predicted by the candidates' perceived influence within their political coalition.